Prophetic Modelling, Habituation, and Spiritual Experience as Mechanisms of Islamic Moral Character Formation: Evidence from Simtudduror Practice in Indonesian Pesantren - Fajrul Falah; Ainol; Sollah Solehudin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Moral character formation in Islamic boarding schools (pesantren) continues to face challenges from digital media influences that erode students' Islamic ethical dispositions, with existing scholarship offering limited analysis of how traditional devotional practices function as internalization mechanisms. This study investigated how Simtudduror recitation a structured reading and explication of Al-Habib Ali Al-Habsyi's mawlid text is implemented at Pondok Pesantren Tarbiyatul Islam Sumberkerang Gending, Probolinggo, Indonesia, and how it contributes to the formation of akhlak mahmudah (noble moral character) in students. A qualitative single case study design was employed with 20 purposively selected participants: one kiai (pesantren director), two tahfidz supervisors, twelve students aged 13–18 with at least one year of programme participation, and five parents. Data were generated across eight observation sessions, twenty in-depth semi-structured interviews, and systematic document analysis. The Miles, Huberman, Saldaña interactive thematic model was applied, with trustworthiness established through source, technique, and time triangulation and member checking. Findings reveal that Simtudduror produces moral character formation through four interlocking mechanisms: (1) repetitive recitation as habituation, (2) syarah (explanatory commentary) as reflective meaning-making, (3) affective-spiritual experience as moral feeling, and (4) ustaz modelling and collective cultural norms as observational learning. Across all five akhlak dimensions measured respect for teachers (ta'dzim), discipline (intizam), humility (tawadu'), self-control (dhabt al-nafs), and religious engagement documented behavioural improvements were gradual, variable, and contextually embedded within the broader pesantren education system. The study offers an empirically grounded four-mechanism model that repositions devotional recitation practice as a theoretically coherent pedagogy of Islamic moral formation, extending Lickona's tripartite character model to devotional educational contexts.